Frida Kahlo and the Feminine - Mushro, Lauren (Colloquium: The Political Science Journal of Boston College, 2018)
This essay outlines Frida Kahlo’s gender representation in her various portraits. Kahlo self-represents various masculine and feminine traits in a variety of her pieces, as evinced through Self-Portrait with Cropped Hair (1940). This androgynous representation has much to do with her familial relationships as well as her relationship with her husband, Diego Rivera. Kahlo additionally also demonstrates her political prowess through artwork such as Moses, and thus brings herself into the masculine political realm. In this essay, Mushro delves into gender constructs, sexuality as a radical weapon, and physical appearance as a challenge to hegemonic masculinity.